Hemeroby reveals the dynamics of vegetation cover following the destruction of the Kakhovka Reservoir - Lisovets,Olena; Podorozhniy,Serhiy; Tutova,Hanna; Molozhon,Karina; Kunakh,Olha; Zhukov,Olexander (PeerJ, 2025)
Floodplain ecosystems play a crucial role in maintaining ecological balance by regulating hydrological regimes, conserving biodiversity, and providing essential ecosystem services. The destruction of the Kakhovka Reservoir in June 2023 resulted in a large-scale environmental disaster that profoundly affected both aquatic and terrestrial ecosystems in the Lower Dnipro region. This study was conducted in the floodplain ecosystems of Khortytsia Island (Ukraine) to assess vegetation changes in response to altered hydrological conditions. Phytosociological mapping of the vegetation cover was performed, and the concept of hemeroby was employed to evaluate the level of anthropogenic transformation of plant communities. Phytoindication scales were utilized to characterize environmental conditions, including humidity, light, and soil properties. Following the destruction of the reservoir, significant changes in the water regime led to the degradation of floodplain water bodies, the expansion of sandy open areas, and the formation of new ecotopes. Twelve distinct plant community associations were identified, each differing in ecological preferences and sensitivity to anthropogenic disturbances. Principal component analysis revealed that most of the variability in plant community composition is explained by gradients in humidity, trophic status, and light availability, all of which are closely associated with hemeroby and naturalness indices. These findings underscore the dominant influence of recent anthropogenic drivers on vegetation structure. A decline in water availability following the reservoir’s destruction emerged as a primary driver of vegetation dynamics in the affected areas. Coastal zones experienced the most pronounced changes, where newly exposed sandy substrates were rapidly colonized by xerophytic and ruderal species, forming highly hemerobic communities. In contrast, more stable conditions in the central part of the island supported the persistence of relatively undisturbed plant assemblages. Increased light levels and elevated soil nutrient content in open areas were also found to promote the spread of species with high hemeroby, reinforcing the connection between altered abiotic conditions and anthropogenic transformation. This study demonstrates that the collapse of the Kakhovka Reservoir triggered rapid shifts in floodplain vegetation, with moisture regime, illumination, and nutrient availability acting as key environmental filters. The observed correspondence between these factors and the level of hemeroby confirms the utility of hemeroby and naturalness indices as effective tools for monitoring post-catastrophic ecological changes and informing future strategies for ecosystem restoration.
Keywords: Hemeroby; Naturalness; Succession; Humidity; Floodplain ecosystems; Anthropogenic impact